Effects of high altitude training on exercise capacity: fact or myth - de Paula, P.; Niebauer, J. (Sleep and Breathing, 2012)
Introduction High altitude training has become a mainstay in endurance sports, with live high-train low as the current protocol of choice. Athletes either live or sleep in artificial or natural hypoxic conditions with the aim to increase serum erythropoietin concentrations, which are thought to improve maximum oxygen uptake and thus exercise performance. Discussion Changes, however, are not very striking and only apparent in so-called responders, who are not a well-defined group and may be as little as 50% of the trained study population. Whereas some studies show minor improvement, others report no change or even worsening. Furthermore, the mechanisms behind the proposed beneficial changes remain obscure and are far from being proven. There is an evident lack of sufficiently powered randomized, double-blinded studies, with training protocols that are identical for all groups and groups that are indeed comparable. Several studies discriminate between responders and non-responders, without clearly assessing the characteristics of the so-called responders. Until this has been done, it remains unclear if such a group really exists and how these subjects are characterized. This, however, would be of immense value, so protocols could be tailored to athletes` needs. Taken together, the current literature on natural or artificial hypoxia somewhat documents improved performance at high but not low altitude.